Analisis Potret Ekonomi Publik Indonesia Meliputi Tanaman Palawija, Perkebunan, Kehutanan, Perternakan Dan Perikanan - Tina Safira; Mohamat Masrur Mauridhoh; Muhammad Yasin (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze the portrait of the Indonesian public economy with a focus on the secondary crops, plantations, forestry, livestock and fisheries sectors. This study uses a descriptive analytical approach to identify the contribution of each sector to the national economy, the challenges faced, and the potential for future development. Data was obtained from various national statistical sources, government reports, and relevant academic literature. The results of the analysis show that these sectors have an important role in providing employment opportunities, increasing regional income, and contributing to national GDP. Secondary crops and plantations, for example, show high potential for economic diversification and food security. The forestry sector, despite facing the challenges of deforestation and climate change, remains significant in providing industrial raw materials and environmental conservation. Livestock and fisheries also play an important role in meeting people's protein needs and supporting food security. However, these various sectors face challenges such as lack of infrastructure, limited market access, and policies that are not yet optimal. This study suggests the need for a more integrated and sustainable development strategy to maximize the contribution of these sectors to the Indonesian economy.